2019
DOI: 10.1136/archdischild-2018-316479
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes in preterm multiples receiving delayed cord clamping

Abstract: ObjectiveTo compare neonatal outcomes in singletons versus multiples, first-born versus second-born multiples and monochorionic versus dichorionic/trichorionic multiples <33 weeks’ gestational age (GA) who received delayed cord clamping (DCC).DesignRetrospective, observational study of 529 preterm infants receiving ≥30 s DCC. Generalised estimating equations and mixed effects models were used to compare outcomes in singletons versus multiples and monochorionic versus dichorionic/trichorionic multiples. Wilcoxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It makes sense to provide them with more of their own blood through placental transfusion at birth [51,52]. Studies of multiple births have demonstrated feasibility of providing OCM to twins and triplets [53,54]. Thus, multiple births should not be routinely excluded.…”
Section: Potential Fetal Risk Conditionsmentioning
confidence: 99%
“…It makes sense to provide them with more of their own blood through placental transfusion at birth [51,52]. Studies of multiple births have demonstrated feasibility of providing OCM to twins and triplets [53,54]. Thus, multiple births should not be routinely excluded.…”
Section: Potential Fetal Risk Conditionsmentioning
confidence: 99%
“…There was no evidence for acute intertwin hemorrhage, and the observed difference was ascribed to differential clamping times [61]. A retrospective observational study showed that multiples less than 33 weeks gestation of mono/di/and tri chorionicity receiving DCC had similar outcomes to singletons receiving DCC [62]. In an RCT of preterm multiples between 28-36 weeks gestation, there was no difference in admission hematocrit between early and delayed clamping groups, but more frequent PPH in the DCC group, which contradicts other studies [63][64][65].…”
Section: Multiple Gestationsmentioning
confidence: 98%
“…The safety profile of OCM in multiple births continues to be debated. Several studies support the practice in these infants, and national guidance suggests suitability should be assessed on a case-by-case basis rather than routine exclusion 13–15. However, in monochorionic twins where there is concern of placental vessel anastomoses (twin-to-twin transfusion syndrome or twin anaemia polycythaemia sequence), there is a risk of draining blood from one twin to the other during the procedure, thus these infants are often excluded from OCM.…”
Section: Introductionmentioning
confidence: 99%